Optimising courier specimen collection time improves patient access to HIV viral load testing in South Africa - Sarah J. Girdwood; Thomas Crompton; Naseem Cassim; Floyd Olsen; Portia Sejake; Karidia Diallo; Leigh Berrie; Dorman Chimhamhiwa; Wendy Stevens; Brooke Nichols (AOSIS, 2022)
Background: South Africa uses a courier network for transporting specimens to public laboratories. After the daily collection of specimens from the facility by the courier, patients not yet attended to are unlikely to receive same-day blood draws, potentially inhibiting access to viral load (VL) testing for HIV patients. Objective: We aimed to design an optimised courier network and assess whether this improves VL testing access. Methods: We optimised the specimen transport network in South Africa for 4046 facilities (November 2019). For facilities with current specimen transport times (n = 356), we assessed the relationship between specimen transport time and VL testing access (number of annual VL tests per antiretroviral treatment patient) using regression analysis. We compared our optimised transport times with courier collection times to determine the change in access to same-day blood draws. Results: The number of annual VL tests per antiretroviral treatment patient (1.14, standard deviation: 0.02) was higher at facilities that had courier collection after 13:36 (the average latest collection time) than those that had their last collection before 13:36 (1.06, standard deviation: 0.03), even when adjusted for facility size. Through network optimisation, the average time for specimen transport was delayed to 14:35, resulting in a 6% - 13% increase in patient access to blood draws. Conclusion: Viral load testing access depends on the time of courier collection at healthcare facilities. Simple solutions are frequently overlooked in the quest to improve healthcare. We demonstrate how simply changing specimen transportation timing could markedly improve access to VL testing.